UNVEILING BRAIN DRAIN, REMITTANCES INFLOWS & ECONOMIC GROWTH NEXUS IN ASIA AT AGGREGATED AND DISAGGREGATED LEVEL - Salman Moazam; Asma Awan (International Journal of Contemporary Issues in Social Sciences, 2024)
A massive increase in brain drain has been observed in recent decades which in turn has multifaceted implications for economic growth. In fact brain drain is an emerging issue in developing countries (in general) and in Asia (in particular). On one side, it hinders economic growth by causing human capital loss. Conversely, it may result in higher remittance inflows that can potentially accelerate economic growth. The complexity of mutual association among brain drain, remittances and economic growth in turn demands more rigorous research. Using balanced panel dataset of 26 Asian economies, this study has analyzed the simultaneous long run relationship among brain drain, inflows of remittances and economic growth from 1996 to 2022 at aggregated and disaggregated level. In addition to pre-estimation tests, the study uses the panel unit root test to guarantee the stationarity of the variables. To estimate simultaneous model comprising of three structural equations, the study uses the Panel 2SLS estimation method after confirming simultaneity, over-identification and other pre-requisites. Furthermore, the study has also constructed index of standard of living, institutional quality, social safety nets, demographic characteristics and infrastructure to make a comprehensive analysis on subject matter. For index construction, PCA method is utilized. The empirical results reveal a bidirectional association between brain drain and remittance inflow in all panels of Asia except low-income economies. The remittances and economic growth also show a bidirectional relationship in Asia (overall), low-middle, and high-income economies. Whereas, low-income and upper- middle-income economies show a unidirectional relationship. The findings also reveal the significant impact of brain drain on remittances at all income levels. The social safety nets, higher living standards, and better institutional quality reduces brain drain, whereas, unemployment and gender inequality increases it. The remittances inflows, labor, capital, and human development are the primary drivers of economic growth along foreign direct investment and institutional quality. Addressing the brain drain, boosting remittance inflows, and fostering economic growth at all income levels require targeted investments in infrastructure, education, jobs, living conditions, governance, and social safety nets.